Hydrogels Improve Plant Growth in Mars Analog Conditions - Peyrusson, Frédéric (Frontiers in Astronomy and Space Sciences, 2021)
Sustainable human settlement on Mars will require in situ resource utilization, the collect and utilization of Mars-based resources, including water and substrates for food production. Plants will be fundamental components of future human missions to Mars, and the question as to whether Mars soils can support plant growth is still open. Moreover, plant cultivation will probably suffer from the lack of in situ water, which might constitute one of the biggest challenges for ISRU-based food production on Mars. Enhancing the crop yield with less water input are thus chief concern for sustainable ISRU food production. Hydrogels are polymers able to absorb large quantity of water and have been shown to increase water retention in the soil and plant growth. This work reports on the short-term assessment of plant growth in Mars soil analogs supplemented with hydrogels, in the constrained environment of a simulated life-on-Mars mission. Soil analogs consisted of sand and clay-rich material, with low amount organic matter and alkaline pH. Soils were sampled in Utah desert, in the vicinity of the Mars Desert Research Station, a Mars analog facility surrounded by soils sharing similarities in mineralogical and chemical composition to Martian soils. Heights and dry biomass of Mentha spicata and seed germination of Raphanus sativus were monitored under various irrigation frequencies. Results indicate that the soil analogs, together with the limited irrigation, were less capable of supporting plant growth as a comparison to potting medium. The effects of hydrogel supplementation were significative under limited irrigation and led to growth increased by 3% and 6% in clay- and sand-containing soils, respectively. Similarly, hydrogel supplementation resulted in plant masses increased by 110% in clay-containing soils and 78% in sand-containing soils. Additionally, while seeds failed to germinate in soil analogs, hydrogel supplementation allows for the germination of 27% of seeds, indicating that hydrogels might help loosening dense media with low water retention. Collectively, the results suggest that supplementation with hydrogel and traditional plant growth substrate could help plants cope with limited irrigation and poor alkaline Mars soil analogs, and are discussed in the context of strategies to develop ISRU for off-world colonization.